(untitled) (Journal of Surgical Sciences, 2013)
Objective: Idiopathic haemorrhoidal disease is a common problem in colorectal practice. Conventional open haemorrhoidectomy is associated with significant pain and an open wound for a long time to heal interfering normal day to day activities. Stapled haemorrhoidopexy is expected to have less pain and without a wound. This study reflects our experience with stapled haemorrhoidopexy in our population. Methods: Two hundred consecutive patients with primary haemorrhoidal disease of different degrees underwent stapled haemorrhoidopexy in BSMMU since January 2009 to April 2011. All the patients were evaluated by history, clinical examination and Proctosigmoidoscopy. With adequate preoperative preparation they underwent stapled haemorrhoidopexy under spinal anaesthesia. They were followed up post-operatively for a median 2 months duration. Results: Male to female ratio was 3.76:1 with median age of 35 years (range: 11-90 years). Median hospital stay was 2 days (24 hours-5 days) and longest 5 days after operation. 14 patients had 1st degree haemorrhoids, 66 patients had 2nd degree haemorrhoids, 104 patients had 3rd degree haemorrhoids and 16 patients had 4th degree haemorrhoids. Median time for the procedure was 25 minutes. Urgency of defecation was complained by 46 patients who ultimately felt comfortable within 2-4 weeks. 6 patients complained of annorectal pain who responded to conventional analgesics. Rest of the patients available after 8 weeks follow up were found to be fully satisfied. Conclusion: Contrary to open haemorrhoidectomy this procedure is associated with least chance of anal incontinence because of preservation of normal anal cushion. It can safely be concluded that stapled haemorrhoidopexy is a better option in treating primary haemorrhoidal disease. DOI: http://dx.doi.org/10.3329/jss.v16i1.14445 Journal of Surgical Sciences (2012) Vol. 16 (1) : 30-34